A rapid and cost effective protocol for plant genomic DNA isolation using regenerated silica columns in combination with CTAB extraction - Ze-yu FU; Jian-cheng SONG; Paula E. Jameson (Journal of Integrative Agriculture, 2017)
Abstract: Isolation of high quality DNA from multiple samples can be both time-consuming and expensive. We have developed a combined protocol to reduce the time component of the hexadecyltrimethylammonium bromide (CTAB) extraction method and reduced costs by regenerating the silica columns used to purify genomic DNA. We present data that shows, by increasing the temperature used during the CTAB method, the time required to extract crude genomic DNA can be reduced. We show that silica columns can be regenerated using HCl and still maintain their DNA-binding capacity. Furthermore, we show both spectrophotometrically, and by restriction enzyme cutting, that the quality of the eluted DNA is high. Critically, using both genomic DNA from pea and perennial ryegrass we demonstrate, using species-specific PCR primers, that there is no carry-over of DNA from repeated use of a single column. The main advantages of the method are high yield, high quality, cost effectiveness and time-saving. This method could satisfy demand when large numbers of plant genomic DNA samples are required, for example from targeting induced local lesions in genomes (TILLING) populations.